THE ANALYSIS OF SERVICE QUALITY AT ARGA JAYA VILLAGE OFFICE, AIR RAMI DISTRICT, MUKO-MUKO REGENCY - Elkana Perangin Angin; Merri Anitasari; Abdul Rahman (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2020)
The purpose of this study was to determine Service Quality at the Arga Jaya Village office, Air Rami District, Muko Muko District. The method used in this research is to use a questionnaire method and the scale used is the Community Satisfaction Survey (SKM) And the results of the service quality questionnaire pembutan Certificate of Disability at the Village Office Arga Jaya District Air Rami Muko-Muko District obtained a score of 82 with the quality of service B with good criteria because it is in the range of SKM Conversion Interval Rates 76.61 - 88.30.